INNOVATIVE EDUCATION IN OUR COUNTRY AND ITS SIGNIFICANCE IN EDUCATION - Karimova Maftuna To’ra qizi (Galaxy International Interdisciplinary Research Journal, 2023)
Many mistakenly believe innovation has to do with the use of technology or new inventions. In “Four Dimensions of Innovation in Education,” Lars Esdal, executive director of Education Evolving, describes innovation in education as doing things in a new way. To do something differently requires coming up with an approach, process, product or strategy.